KEPEMIMPINAN PENDIDIKAN ISLAM DI MADRASAH TSANAWIYAH RIYADLUL JANNAH - Sri Nurlita; Yosa Sobariah, Adi Rosadi (ADISAM PUBLISHER, 2025)
Leadership cannot be separated from social life, Leadership becomes a profession, not the result of heredity, but a person's will, ability, ability and ability to understand the principles of healthy leadership, use the best leadership principles, systems, methods and techniques, understand the basic concepts of leadership, and think carefully. In the process of educational leadership, it can generally be seen from the forms of activity leaders have characteristics, which include firstly pioneering creative efforts in educational and teaching activities, guiding, instructing, mobilizing, coordinating and advancing activities that are part of the institution carrying out the effort. education and teaching like schools as educational institutions. This research is a qualitative descriptive study designed to obtain information about a symptom at the time the research was conducted. The highest leadership in formal educational institutions is the principal who aims to make the school run well, namely by making various efforts made by the principal, one of which is making rules that are implemented well, making efforts to collaborate with various agencies to support the progress of the school, and carrying out approach with students to motivate learning. Apart from that, there are efforts from the school principal to motivate students to study hard and have good morals in order to achieve the school's vision and mission. The task of a leader is to be able to establish relationships both internally, namely with teachers, employees and students, and externally, namely with related institutions or agencies, being able to apply leadership principles and collaborate